Il Metodo Psycofilm Cinema e Psico-Oncologia - Paola Dei (Phenomena Journal)
At the Valdelsa donna Association, in collaboration with the USL Toscana SudEst Campostaggia Siena, directed by oncologist dr. Angelo Martignetti, in the years 2012-2013 a Cinema-thérapy project was carried out with the Psycofilm Method, a registered trademark, developed by Paola Dei President of the Center for the Study of Art Psychology and Expressive Psychotherapy, which made use of the discovery of Neurons Mirror by Giacomo Rizzolatti and his team, of the principles of Psychology of Art, in particular by Rudolf Arnheim, to which notes of the Enneagram of Claudio Naranjo have been added sometimes. In addition, John Bowlby’s Theory of Attachment has sometimes been used. The project born the need to offer life to the years of cancer patients and people who have lost loved ones, through an approach defined “aestetic-experimental” (experimental aesthetics) has proposed to assess the importance of working through cinema in order to highlight the emotional transformations and changes in the feelings felt towards oneself and towards others within family relationships or significant relationships. This entailed the implementation of strategies which presupposed the development of creativity. The emotional reconstruction elaborated through a creative path that acted as a mirror of one's own experiences, activating it, in turn in the observer, allowed the partecipants to sustain painful experiences and transform them into artistic works. The work has been interpreted through scientific tests that have provided interesting result for future research developments.